Optimizing the use of lenvatinib in combination with pembrolizumab in patients with advanced endometrial carcinoma - Lorusso, Domenica; Danesi, Romano; Locati, Laura Deborah; Masi, Gianluca; De Giorgi, Ugo; Gadducci, Angiolo; Pignata, Sandro; Sabbatini, Roberto; Savarese, Antonella; Valabrega, Giorgio; Zamagni, Claudio; Colombo, Nicoletta (Frontiers in Oncology, 2022)
Introduction The combination of lenvatinib plus pembrolizumab demonstrated a relevant clinical benefit in patients with endometrial carcinoma. The safety profile was consistent with the established profiles of each drug in monotherapy, with the most frequent adverse events being hypertension, an on-target effect, hypothyroidism, diarrhea, nausea, vomiting, loss of appetite, fatigue, and weight loss. Areas covered We first review the rationale based on the combination of a VEGFR inhibitor and an immune checkpoint inhibitor, highlighting the main pharmacokinetic and pharmacodynamic features of lenvatinib. Next, we focus on the common adverse events associated with lenvatinib and guide how to optimally prevent, detect, and manage them, while minimizing interruptions during lenvatinib treatment. Discussion The side effects profile of lenvatinib is very well known, being similar across different tumor types. Most toxicities can be preventable. An appropriate, proactive, and thorough management of lenvatinib toxicities during treatment is required to maximize potential lenvatinib efficacy. Adverse events should be detected as early as possible, by both carefully monitoring the patient from lenvatinib initiation and preventing their occurrence. Patients should be followed also during treatment as some adverse events, e.g., cardiac dysfunction might appear later. Increased awareness on risk to benefit ratio among clinicians would be helpful to avoid dose interruptions or discontinuation of lenvatinib, with preferring other medical interventions and supportive care.